ARCHITECTURAL UTOPIA AND POLITICAL VIOLENCE IN NGUGI WA THIANG’O’S WIZARD OF THE CROW - Mustapha , Bala Ruma (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
This paper explores the intersection of landscape, architectural design, political violence and Literature. It specifically focuses on the stimulating influence of landscape and architectural designs on the imaginative faculty of Ngugi in his 2007 novel Wizard of the Crow. The paper critically examines his employment of architectural tropes to shape a gripping narrative about corruption, greed, violence and wastefulness in the fictional African nation of Aburiria; a prototype of most African nations. The paper also examines how Ngugi explores the dysfunctional nature of most African cities especially in matters of hygiene, waste management, and environmental conservation/destruction. The paper concludes that there is a very close connection between building / construction business, environmental destruction, political violence and corruption in the Aburῑrian nation, as complexly depicted in the novel. This is very disturbing because it reminds us of the painful fact that whereas elsewhere in the world buildings and other architectural masterpieces are signs of progress and development, in Africa they are conduits for siphoning funds often sourced through dubious loans by those in positions of leadership as demonstrated in Wizard of the Crow.